Computational modeling of attractor-based neural processes involved in the preparation of voluntary actions - Hassannejad Nazir, Azadeh; Hellgren Kotaleski, Jeanette; Liljenström, Hans (Cognitive neurodynamics, 2024)
Volition is conceived as a set of orchestrated executive functions, which can be characterized by features, such as reason-based and goal-directedness, driven by endogenous signals. The lateral prefrontal cortex (LPFC) has long been considered to be responsible for cognitive control and executive function, and its neurodynamics appears to be central to goal-directed cognition. In order to address both associative processes (i.e. reason-action and action-outcome) based on internal stimuli, it seems essential to consider the interconnectivity of LPFC and the anterior cingulate cortex (ACC). The critical placement of ACC as a hub mediates projection of afferent expectancy signals directly from brain structures associated with emotion, as well as internal signals from subcortical areas to the LPFC. Apparently, the two cortical areas LPFC and ACC play a pivotal role in the formation of voluntary behaviors. In this paper, we model the neurodynamics of these two neural structures and their interactions related to intentional control. We predict that the emergence of intention is the result of both feedback-based and competitive mechanisms among neural attractors. These mechanisms alter the dimensionalities of coexisting chaotic attractors to more stable, low dimensional manifolds as limit cycle attractors, which may result in the onset of a readiness potential (RP) in SMA, associated with a decision to act.